ENERGY ANALYSIS OF A SOLAR AIR HEATER WITH AN ABSORBER PLATE MADE OF POROUS MATERIAL - Ozgen, Filiz; Dayan, Ayse (Vinca Inst Nuclear Sci, 2021)
In this study, the energy analysis of a solar air heater with an absorber plate made of different obstacles was made. Absorber plate of the solar air heater was created with porous steel wool. Three different absorber plates were used for the experimental study. Complex plate (Type I) was used as the first type of absorber plate, less complex plate (Type II) as the second type absorber plate, and flat plate (Type III) the third type absorber plate. On these plates, which are manufactured as three different absorber plates, steel wools are placed in a complex and less complex way. One absorber plate was left empty. In the experiments, the mass-flow rate of the air passing through the air passage channels was taken as 0.05 kg/s and 0.025 kg/s, and the optimum flow rate was found as 0.05 kg/s. In order to make heater efficiency calculations, heater inlet temperature, outlet temperature, absorber plate temperature, ambient temperature and solar radiation values were measured. Efficiency values for different absorber plate were found between 23% and 74%.
Keywords: solar heater; absorber plate; obstacle; energy; thermal efficiency